Whole-body vibration and musculoskeletal diseases in professional truck drivers - Geraldo Fabiano de Souza Moraes; Rosana Ferreira Sampaio; Luiz Felipe Silva; Mariana Angélica Peixoto Souza
Abstract Background: Most occupational diseases do not fit the paradigm of medical interpretation of the health-disease process based on linear causality, in which it would be possible to find a single cause for each type of disease. Objectives: to conduct a systematic review in order to investigate the association between whole-body vibration (WBV) and musculoskeletal disorders (MSD) in professional truck drivers (PTD). Methods: The scientific databases of PubMed, Cochrane, Lilacs and Scielo were used to collect articles published from 2000 until the present time. Two independent reviewers adopted inclusion and quality criteria to evaluate the selected articles. Results: From adopted inclusion and quality criteria, nine articles were chosen to identify the association between MSD and WBV in PTD. The results showed that MSD seems to be closely associated to exposure to WBV in these workers, mainly due to high prevalence and symptoms of low back pain. Two cohort studies showed exposure to WBV as risk for MSD. Only one, with case-control design, did not show WBV as a significant factor. Conclusions: In this study the importance of exposure analysis of WBV in the occurrence of MSD in PTD was elucidated. This study showed the importance of WBV exposure analysis on the occurrence of MSD in PTD. There is adequate information to provide rationale for the reduction of WBV exposure to the lowest possible level, to ensure the health of these workers. Studies with a greater power of investigation, of a prospective, design, should be encouraged, supplanting those only of association.